Time-Intensity Curve parametric imaging as a novel quantitative biomarker: enhancing diagnostic accuracy and inter-rater reliability in prostate cancer ultrasound - Zhou, You; Liu, Mingyou; Zhou, Jiguang; Lin, Hanzong; Lan, Jinxin; Xu, Yusheng; Yang, Xiao; Chen, Ming (Frontiers in Oncology, 2025)
ObjectiveTo investigate the diagnostic utility of a novel Time-Intensity Curve (TIC) parametric imaging technique for improving the accuracy of prostate cancer (PCa) detection. This study aimed to quantitatively assess the technology’s impact on the diagnostic performance of ultrasound physicians with disparate levels of clinical experience and to evaluate its potential to standardize diagnostic interpretation.MethodsWe conducted a retrospective analysis of 62 patients who underwent transrectal contrast-enhanced ultrasound (TR-CEUS) at Zhangzhou Affiliated Hospital of Fujian Medical University between December 2024 and March 2025. All diagnoses were confirmed by systematic 12-core prostate biopsy. A proprietary TIC parametric imaging software was used to perform a pixel-wise analysis of CEUS cineloops, generating quantitative maps of the perfusion parameter “mean gradient to peak.” These maps were then qualitatively classified based on the spatial heterogeneity of perfusion into a four-tier discreteness system. Four junior physicians (1–2 years experience) and four senior physicians (>10 years experience) independently evaluated patient cases, first using conventional grayscale and CEUS images, and then again after a washout period with the addition of the TIC parametric maps. A paired chi-square test compared diagnostic outcomes. Inter-rater and intra-rater reliability were assessed using intra-class correlation coefficients (ICC). Diagnostic performance was evaluated using Receiver Operating Characteristic (ROC) curve analysis, with Area Under the Curve (AUC) as the primary metric.ResultsA paired chi-square test demonstrated a statistically significant improvement in diagnostic accuracy when TIC parametric imaging was used as an adjunct to conventional ultrasound (p < 0.0001). The introduction of TIC maps markedly improved intra-group diagnostic consistency; the ICC for junior physicians increased from a good 0.832 to an excellent 0.915, and for senior physicians, it rose from an excellent 0.878 to a near-perfect 0.941. Most notably, the diagnostic performance gap between experience levels was effectively eliminated. The AUC for junior physicians surged from 0.43 (95% CI: 0.36-0.50) to 0.85 (95% CI: 0.79-0.90; p < 0.0001). For senior physicians, the AUC improved from 0.53 (95% CI: 0.46-0.60) to an outstanding 0.95 (95% CI: 0.92-0.99; p < 0.0001). With TIC assistance, the diagnostic efficacy of both junior and senior physicians converged at a high level of performance.ConclusionTIC parametric imaging, through its ability to objectively quantify and visualize the spatial heterogeneity of tumor blood perfusion, serves as a powerful adjunctive tool that significantly enhances the accuracy and consistency of prostate cancer diagnosis. This technology demonstrates profound clinical value by substantially mitigating the influence of operator experience, thereby shortening the learning curve for novice physicians and standardizing diagnostic quality across all levels of expertise. the sample size is relatively small, which can lead to wide sensitivity confidence intervals and increases the risk of statistical anomalies. require validation in larger, multi-center prospective trials.